A CASE STUDY ON LINGUISTIC ERRORS IN ARABIC LANGUAGE LEARNING AT STATE ISLAMIC SENIOR HIGH SCHOOL (MAN) INSAN CENDEKIA BATAM CITY - Pakpahan, Tauhid; Salam, Muhammad Yusuf (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This study investigates linguistic errors in Arabic language learning among students at State Islamic Senior High School Insan Cendekia Kota Batam through an ethnographic approach. The research addresses challenges faced by non-native learners, particularly in phonology, morphology, and syntax. The study aims to identify types of errors, analyze their causes, and explore institutional responses. Data were collected through classroom observation, interviews with students, teachers, and administrators, and analysis of teaching materials and student work. Findings reveal frequent errors in the pronunciation of Arabic phonemes such as /ذ/, /ث/, and /ع/, incorrect verb conjugation, and flawed sentence structures. These are primarily caused by first language interference, limited prior exposure to Arabic, lack of structured morphology instruction, and constrained practice time due to tight academic schedules. Arabic instruction tends to be vocabulary-centered, often reducing learning to memorization. The study concludes that a more communicative, contextual, and skill-oriented approach is needed in non-pesantren Islamic schools to improve Arabic proficiency.